Postharvest physiological disorders in fruits and vegetables - Freitas, Sergio Tonetto de; Pareek, Sunil (Boca Raton, FL : CRC Press, Taylor & Francis Group, 2019)
This book, chock full of color illustrations, addresses the main postharvest physiological disorders studied in fruits and vegetables. For a wide variety of fruits and vegetables, Postharvest Physiological Disorders in Fruits and Vegetables describes visual symptoms, triggering and inhibiting mechanisms, and approaches to predict and control these disorders after harvest. Color photographs illustrate the disorders, important factors, physiology, and management. The book includes a detailed description of the visual symptoms, triggering and inhibiting mechanisms, and possible approaches to predict and control physiological disorders. The mechanisms triggering and inhibiting the disorders are discussed in detail in each chapter, based on recent studies, which can help readers better understand the factors regulating each disorder. The description of possible approaches to predict and control each disorder can help growers, shippers, wholesalers, and retailers to determine the best management practices to reduce disorder incidence and crop losses. Features: Presents visual symptoms of postharvest physiological disorders that will help readers to precisely identify the disorders in fruits and vegetables Details mechanisms triggering and inhibiting the postharvest disorders Explains possible approaches to predict and control these disorders Suggests the best postharvest management approaches for each crop Although there are many scientific publications on postharvest physiological disorders, there are no recent reviews or books putting together the most recent information about the mechanisms regulating, as well as about the possible approaches to predict and control these disorders.
OCLC-licensed vendor bibliographic record.
Keywords: Crops -- Postharvest physiology; Fruit -- Postharvest diseases and injuries; Vegetables -- Postharvest diseases and injuries; GARDENING / Essays; GARDENING / Reference; GARDENING / Vegetables; SCIENCE / Life Sciences / Horticulture; TECHNOLOGY / Agriculture / General; TECHNOLOGY / Food Science